PENGEMBANGAN APLIKASI PENILAIAN SENAM AEROBIK PADA PUSAT PENDIDIKAN DAN LATIHAN OLAHRAGA PELAJAR (PPLP) PROVINSI JAMBI - Fitri Khairunnisa; Ilham; Atri Widowati; Ugi Nugraha; Sukendro (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an Android-based Smart Point application as an innovation in the aerobic gymnastics scoring system, specifically for PPLP aerobic gymnastics. The background of this research is the judging process that is still done manually using assessment paper, so it is prone to errors and is inefficient and makes it easier to conduct control tests on PPLP athletes before the competition. The method used is Research and Development (R&D) with the Borg and Gall model consisting of ten stages of development, from analysis to product implementation. The research subjects involved aerobic gymnastics judges, media experts, and material experts. The research instrument used a validation questionnaire and a Likert-based trial. The results showed that the assessment application called Smart Point has a high level of feasibility with validation from material experts 95.50%, media experts 93%, and language experts 94.25%. User trials showed that this application is practical, efficient, and able to speed up the score recapitulation process by up to 50%. The Smart Point application is considered effective in increasing the objectivity and efficiency of assessment in aerobic gymnastics competitions.